1983
DOI: 10.1577/1548-8659(1983)112<638:aneozr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Estimate of Zooplankton Retention by Gill Rakers and Its Ecological Significance

Abstract: The probability that prey will be retained by gill rakers of white crappies Pomoxis annularis (9–15 cm total length) was determined by comparisons of size‐frequency distributions of prey in a laboratory pool and in stomach contents. White crappies trained to feed on large‐bodied Daphnia magna were released individually into a pool containing that species and an assemblage of small‐bodied species. Most attacks were directed at Daphnia magna, but several prey were ingested for every attack, and nonselective capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Observations on fourth-instar C. crystallinus feeding on small prey consistently resulted in more prey in the crops than the number of strikes made with the head capsule. These "extra" prey could have been captured incidentally while the larvae struck at other prey items, a phenomenon well described for planktivorous fish (Wright et al 1983). Giguere and Dill (1983) suggested that the mandibular fans might be used for filter feeding.…”
Section: Discussionmentioning
confidence: 96%
“…Observations on fourth-instar C. crystallinus feeding on small prey consistently resulted in more prey in the crops than the number of strikes made with the head capsule. These "extra" prey could have been captured incidentally while the larvae struck at other prey items, a phenomenon well described for planktivorous fish (Wright et al 1983). Giguere and Dill (1983) suggested that the mandibular fans might be used for filter feeding.…”
Section: Discussionmentioning
confidence: 96%
“…bacteria attached to particles). There is a minimum-sized particle that can be retained on the gill rakers of a species (Wright et al 1983). Therefore, there are size classes of plankton that should be too small for certain fish species to consume.…”
Section: Discussionmentioning
confidence: 99%
“…Previous s t u h e s on filter-feeding fishes have shown that as food particle size increases feeding efficiency also increases (Wright et al 1983, Friedland et al 1984. McIntyre (1983) found that gizzard shad Dorosoma cepedianum collected 24 times more food from tanks in which algal flocculation was induced by adding clay particles to the water, as compared to tanks without flocculation.…”
Section: Introductionmentioning
confidence: 97%
“…Helostoma temmincki (Liem, 1967); l Centrarchidae: bluegill sunfish, Lepomis macrochirus (Werner, 1972(Werner, , 1974(Werner, , 1977Werner & Hall, 1974Vinyard & O'Brien, 1975O'Brien et al, 1976;Werner et al, , 1981Werner et al, , 1983aWerner et al, , 1983bVinyard, 1980;Gardner, 1981;Mittelbach, 1981;Janssen, 1982); northern longear sunfish, Lepomis megalotis peltastes, and pumpkinseed, L. gibbosus (Laughlin & Werner, 1980); white crappie, Pomoxis annularis (Wright et al, 1983;Wright & O'Brien, 1984); largemouth bass fry, Micropterus salmoides (Elliot, 1976); l Percidae: Eurasian perch, Perca fluviatilis (Guma'a, 1978;Furnass, 1979;Stenson, 1980); yellow perch, Z? flavescens (Galbraith, 1967;Wong & Ward, 1972;Rasmussen, 1973); l Cichlidae: Congo tilapia, Tilapia rendalli (Caulton, 1976); blue tilapia, 7: aurea (Spataru & Zorn, 1978;Gophen et al, 1983aGophen et al, , 1983bDrenner et al, 1984b); 7Y esculenta (Greenwood, 1953); T nilotica (Moriarty, 1973;Moriarty & Moriarty, 1973); Sarotherodon galilaeus (Lauzanne & Iltis, 1975;Spataru, 1976;Spataru & Zorn, 1976;Lauzanne, 1977;Gophen, 1980;…”
Section: Contentsmentioning
confidence: 99%
“…Nevertheless, several prey may be inhaled incidentally during the capture of the pursued prey (Wright et al, 1983).…”
Section: A Obligate and Facultative Planktivoresmentioning
confidence: 99%